Penerapan Value Engineering Untuk Meminimalisir Faktor Penyebab Adanya Sisa Material Konstruksi - haryanto (Jurnal Civil Engineering Study, 2023)
In the implementation of a project there are problems that still need to be examined again in the world of construction related to effectiveness, efficiency and economy. One of the closest ways is the application of value engineering in construction projects. The Value Engineering Analysis method has advantages, namely the existence of a systematic, neat, and organized approach in analyzing the value (value) of the subject matter of the function but still consistent with the needs for the appearance, quality, and maintenance of the project. Stages of Value Engineering, namely: the information stage of the Value Engineering process includes formulating problems, collecting data, getting to know objects (products) by reviewing functions and recording costs. Based on the results of the analysis and evaluation that has been carried out for the calculation of the remaining material (waste) in the Construction Project for the Madrasah Tsanawiyah Negeri 2 Building (Building A) which is the cause of the occurrence of material waste including: (a) the human factor indicator has a mean value of 2.98 and rank 1; (b) field factor indicators have a mean value of 3.06 and rank 1; (c) the material procurement indicator has a mean value of 2.90 and rank 1; (d) the work method indicator has a mean value of 3.08 and a ranking of 1; and (e) the Tool/Machine indicator has a mean value of 2.98 and a ranking of 1. From the results of value engineering calculations, the cost of the construction of the State 2 Madrasah Tsanawiyah Building Project (Building A) is saved in the amount of Rp. 70,788,369.43.